Global advancement of cooling technologies for PV systems: A review. (1st November 2016) - Hasanuzzaman, M.; Malek, A.B.M.A.; Islam, M.M.; Pandey, A.K.; Rahim, N.A.
Highlights: Thermal model of a PV module from both energy and exergy viewpoints. Brief review on the impact of temperature rise on PV module performance. Comprehensive overview on recently developed PV module cooling technologies. Passive cooling technologies including the use of phase change material. Future countenance in PV cooling research. Abstract: Photovoltaic (PV) systems operate in a paradox; sunlight is the essential input to generate electricity with PV, but they suffer a digression in performance as the operating temperature goes higher. This work is a comprehensive compilation and review of the latest literature regarding research works rendered to achieve improved efficiency through appropriate cooling systems. Most of the research goals were twofold, that is to enhance the efficiency of the solar PV systems and to ensure a longer life at the same time. The passive cooling systems are found to achieve a reduction in PV module temperature in the range of 6–20 °C with an improvement in electrical efficiency up to 15.5% maximum. On the other side, active cooling systems' performance are better, as may expected, with a reduction in PV module temperature as high as 30 °C with an improvement in electrical efficiency up to 22% maximum along with additional thermal energy output with efficiency reaching as high as 60%. Based on the wide-ranging review, it may be predicted that with the swelling growth of solar PV electricity worldwide, the compatible cooling system is becoming obligatory in order to ensure better energy harvest and utilization.